The use of fiber from oil palm trunk (OPTF) as a concrete fibrous reinforcement / Prof. Madya Zakiah Ahmad and Dr Hamidah Mohd Saman - Ahmad, Zakiah; Mohd Saman, Hamidah (2001)
Concrete has high compressive strength, stiffness, low thermal, low electrical conductivity and low toxic. However, concrete is brittle and weak in tension. When subjected to tensile stress, unreinforced concrete will crack and fail. Reinforcement with randomly distributed short fibers presents an effective approach to curb the crack propagation and improving the ductility and tensile strength of concrete. Malaysia is the largest palm oil producer and contributes about 57.6% of the total supply of palm oil in the world. Intensive plantation was started in the 1960's. Since the average economic life of the oil palm is estimated at around 25 years, a large amount of the trunk is available during replanting by 1985. As the housing development increase, a lot more of oil palm estate have been cleared. The felled off oil palm trunks creates environmental pollution as it encourage fungal and infestation to the young trees. The utilisation of oil palm trunk fiber will be advantages into two folds. First, saving the cost as alternative fiber to replace synthetic fiber for used in concrete as reinforcement. Second, the economic way of disposal of oil palm byproduct and create healthy environment.